2021
DOI: 10.1016/j.immuni.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy modulates endothelial junctions to restrain neutrophil diapedesis during inflammation

Abstract: Summary The migration of neutrophils from the blood circulation to sites of infection or injury is a key immune response and requires the breaching of endothelial cells (ECs) that line the inner aspect of blood vessels. Unregulated neutrophil transendothelial cell migration (TEM) is pathogenic, but the molecular basis of its physiological termination remains unknown. Here, we demonstrated that ECs of venules in inflamed tissues exhibited a robust autophagic response that was aligned temporally with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 84 publications
0
49
0
Order By: Relevance
“…In fact, unregulated autophagy is involved in epidermal differentiation defects, and it has also been shown to be involved in dermatological diseases [12,13]. Moreover, autophagy deficiency in EC results in unregulated leukocyte transendothelial migration, increasing neutrophil infiltration and tissue damage [14]. Moreover, our results showed that PASH patients showed alterations in the cell surface interactions at the vascular wall (R-HSA-202733) pathway.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, unregulated autophagy is involved in epidermal differentiation defects, and it has also been shown to be involved in dermatological diseases [12,13]. Moreover, autophagy deficiency in EC results in unregulated leukocyte transendothelial migration, increasing neutrophil infiltration and tissue damage [14]. Moreover, our results showed that PASH patients showed alterations in the cell surface interactions at the vascular wall (R-HSA-202733) pathway.…”
Section: Discussionmentioning
confidence: 60%
“…Autophagy in enterocytes also lowers sensitivity to ROS induced by commensal bacteria, via suppression of p62 and Hippo pathway genes, to maintain septate junction integrity and attenuate dysplasia 62 . Maintenance of cell junctions by increased autophagy is not restricted to epithelial tissue; for example, this occurs acutely in mammalian endothelial cells to prevent excessive diapedesis of neutrophils in inflammatory responses 63 . Here, we demonstrate a link between enterocyte sex, the histone-Bchs axis, junctional integrity, and lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…However, light scattering and out-of-focus fluorescence emission limit the depths that can be achieved by conventional confocal imaging. Therefore, confocal IVM is best applied in organs that require imaging at depths less than ~50 μm, such as organs where neutrophil recruitment and function can be observed in close proximity to the surface (e.g., skin [ 19 ], liver [ 20 ], lung [ 21 , 22 ], skeletal muscle [ 15 , 23 ], brain/meningeal vasculature [ 24 ], and others).…”
Section: Seeing Is Believing—in Vivo Imaging Of Neutrophil Trafficking and Functionmentioning
confidence: 99%
“…This includes advances in microscopy technology as well as mouse models and imaging applications. For example, recent studies combining advanced IVM imaging with transgenic reporter mouse models have led to the discovery and characterization of previously unrecognized trafficking behaviors of neutrophils at the site of inflammation such as reverse transendothelial migration (rTEM, the movement of neutrophils out of inflamed tissues back into the bloodstream) [ 31 , 32 , 33 ], as well as novel mechanisms that restrain neutrophil infiltration to limit excessive inflammation involving endothelial cell autophagy [ 23 ]. In addition, there have been a number of recent advancements in microscopy technology that allow much larger volumes of tissue to be imaged simultaneously, allowing researchers to study organ-level spatial regulation of immune function.…”
Section: Seeing Is Believing—in Vivo Imaging Of Neutrophil Trafficking and Functionmentioning
confidence: 99%